The success of Church of God-Kenya projects in poverty alleviation in Emuhaya District, Western Kenya - Hezekiah, Obwoge; Onkware, Kennedy; Iteyo, Crispinous (AJP, 2017)
Purpose: The purpose of the study was to examine the success of CoG-Kenya projects in poverty alleviation in Emuhaya District, Western Kenya Methodology: This study was a cross-sectional research that sought to give an examining and descriptive scrutiny of the CoG-K‟s activities in Emuhaya District of Western Kenya. This study sampled a total of 312 respondents (1 Bishop, 1 General Secretary, 1 General Assembly Trustee, 1 General Assembly Treasurer, 16 Directors, 282 Pastors, and 10 Elders) through purposive sampling method. Oral interviews, questionnaire methods and focus group discussion were used to collect data from the respondents. Observation method was used to validate the information obtained through oral interviews and questionnaires. Secondary data was sourced from published and unpublished literature. Data was analyzed using the theological method of induction (TMI). Results: The study proved that the CoG-K has a role to play through her programs like Sisi kwa Sisi, Child Development Centres, Health care Units and education, thus these institutions make a significant contribution to sustainable development in Emuhaya District and are useful instruments for spearheading alleviation of poverty in the said district. The CoG-K‟s development is founded upon a spirituality of mutual sustenance and transformation through its concern for the adherents‟ struggle with poverty. This study found out that faith activities and the related projects implicitly advance the poverty alleviation cause, thus all development revolves around spirituality. From this perspective the CoG-K has the responsibility to engage in all aspects of development within spirituality as the foundation of such engagement. Unique contribution to theory, practice and policy: The study recommends that development experts, theologians, policy makers and practitioners should cultivate long-term relationship with the church in general and the CoG-K in particular so as implement policy for development consequently alleviating poverty.
Keywords: CoG-K projects; poverty alleviation; Emuhaya District; Western Kenya